THE IMPACT OF MIGRANTS’ REMITTANCES ON ECONOMIC GROWTH EMPIRICAL STUDY: CASE OF ALGERIA (1970-2010) - Belmimoun, Abdennour; Kerbouche, Mohammed; Adouka, Lakhdar; Mokeddem, Rima (European Scientific Journal, ESJ, 2014)
This paper aims to study the impact of Migrants’ remittances on the Algerian economy in the short and long term, using Vector Error Correction Model (VECM). The model included some variable which are: The dependent variable represented by GDP per capita and independent variables represented by Remittances (R), Gross fixed capital formation,(GFCF) and Household final consumption expenditure(HFCE).The results show that the remittances have a negative impact on Algerian economy in both short and long term, since the increase in remittances by 1% will lead to a decline in GDP per capita by 0.02 % in the short term, and by 0.006 % in long term and this corresponds with previous studies and approaches.